Game of thrones. The complete seventh season [videorecording (DVD)] - Benioff, David; Weiss, D. B. (Distributed by Warner Home Video, 2017)
The long winter is here. The penultimate Season 7 of this blockbuster hit series focuses on a convergence of armies and attitudes that have been brewing for years.